Strategies for attracting and retaining educators: What does the evidence say? - Podolsky, Anne; Kini, Tara; Darling-Hammond, Linda; Bishop, Joseph (Education Policy Analysis Archives, 2019)
A highly competent teacher workforce is a necessary foundation for improving children’s educational outcomes, especially for those who rely most on schools for their success. Yet in the United States, shortages in the teaching force have been growing across the country, reaching crisis proportions in some teaching fields— such as mathematics, science, and special education—and in locations where wages and working conditions are least attractive. We analyzed recent research and representative survey data to identify the drivers of teacher recruitment and retention. We also reviewed the policy literature to identify district, state, and federal policy strategies that have been effective at addressing the factors influencing teachers’ professional decisions. These policies include increasing their compensation and improving their preparation, professional support, and working conditions, as well as improving district and school management practices that otherwise create obstacles to recruitment and retention.